2016
DOI: 10.21010/ajtcam.v14i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Composition and Nutritional Evaluation of Barley Rihane (Hordeum Vulgare L)

Abstract: Background: Many experimental studies have suggested an important role for barley Rihane(BR)in the prevention of colon cancer and cardiovascular diseases. The objective of this study was to evaluate the physico-chemical properties and nutritional characterizations of BR compared to other varieties grown in Tunisia (Manel, Roho and Tej). Material and Methods: Total, insoluble and soluble dietary fiber(β-glucan),total protein, ash and some minerals of BR and Tunisian barley varieties were determined. Results:The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
7
16
0
Order By: Relevance
“…The results obtained here for the phenolic compounds were similar to those obtained by Abdel‐Aal and Choo (2014) and Lahouar et al. (2017) and higher than those reported by Ragaee et al. (2006).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results obtained here for the phenolic compounds were similar to those obtained by Abdel‐Aal and Choo (2014) and Lahouar et al. (2017) and higher than those reported by Ragaee et al. (2006).…”
Section: Resultssupporting
confidence: 91%
“…(2006) and Lahouar et al. (2017). Potassium and magnesium contents were similar to phosphorous, which is within the range described by Woźniak et al.…”
Section: Resultsmentioning
confidence: 96%
“…Their contribution toward the nutritional value and storage stability of barley-based food or feed is important. Lahouar et al [41] demonstrated that the main components of the unsaturated fatty acids in barley were oleic acid, linoleic acid, and α-linolenic acid. Distribution of fats among more endosperm fractions is clear (C1-C3 > B1-B3).…”
Section: Yield and Chemical Characterisation Of Milling Fractionsmentioning
confidence: 99%
“…Functional ingredients of barley with antioxidative and immunomodulatory activities are associated with anticancer effects [18]. Barley with high dietary fiber (β-glucan) has an important role for the prevention of colon cancer and cardiovascular diseases [99]; low molecular weight β-d-glucan can enhance antioxidant and antiproliferative activities [100]. Aqueous extract of fermented barley can induce subcutaneous transplantation tumor apoptosis that can be used for a nutrient supplement in the treatment of human colon cancer [101].…”
Section: Cardiovascular Disease Preventionmentioning
confidence: 99%